Option Coskewness and Capital Asset Pricing - Vanden, Joel M. (Review of Financial Studies, 2006)
This article shows how the market coskewness model of Rubinstein (1973) and Kraus and Litzenberger (1976) is altered when a nonredundant call option is optimally traded. Owing to the option’s nonredundancy, the economy’s stochastic discount factor (SDF) depends not only on the market return and the square of the market return but also on the option return, the square of the option return, and the product of the market and option returns. This leads to an asset pricing model in which the expected return on any risky asset depends explicitly on the asset’s coskewness with option returns. The empirical results show that the option coskewness model outperforms several competing benchmark models. Furthermore, option coskewness captures some of the same risks as the Fama–French factors small minus big (SMB) and high minus low (HML). These results suggest that the factors that drive the pricing of nonredundant options are also important for pricing risky equities.(JEL G11, G12, D61)